Superhydrophobic Polymer-particle Composite Films Produced Using Various Particle Sizes - Karapanagiotis, Ioannis; Manoudis, Panagiotis N.; Savva, Achilleas; Panayiotou, Costas (My University, 2012)
Hydrophilic alumina (Al 2O 3) nanoparticles (25, 35, and 150 nm) are dispersed in different concentrations in solutions of a commercial hydrophobic poly(alkyl siloxane) (Silres BS-290), and the suspensions are sprayed on glass surfaces. Static contact angles (θ S), measured on surfaces of siloxane-nanoparticle composite films that were prepared from dilute dispersions, increase rapidly with particle concentration. Composite films prepared from concentrated dispersions exhibit a maximum, constant θ S (at saturation θ S is 160°), which is not affected by the size of the particles. These films exhibit also very small contact angle hysteresis (5°), which is also independent of the particle size. Consequently, the same superhydrophobic character can be induced in siloxane films using nanoparticles, which can range from a few up to several tenths of nanometers. However, the particle size and more precisely the particle specific surface area affects dramatically the minimum critical particle concentration, which must be used in the dispersions to induce superhydrophobicity on the surface of the composite films, that is, to achieve θ S = 150°. It is shown that critical particle concentration decreases exponentially with specific surface area. This result can be important for manufacturers of superhydrophobic surfaces who are interested in having a good control on the wettability of the composite films. Copyright © 2012 John Wiley & Sons, Ltd.
Keywords: Contact angle; Nanoparticle; Superhydrophobic surface; Water repellency